2021
DOI: 10.1109/access.2021.3131980
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis of CSDG MOSFET With La2O3 Gate Oxide: Based on Electrical Field Estimation

Abstract: Cylindrical Surrounding Double-Gate (CSDG) MOSFETs have been designed for a suitable CMOS replacement to diminish the power and area tradeoff. With these MOSFETs below 70 nm node for Semiconductor Industry Association (SIA) roadmap, the CMOS technology has excellent immunity to the Short Channel Effects (SCE) and better scalability. To reduce the SCE, the device was analyzed by improving the gate oxide thickness between the gate terminal and channel material and replacing the conventional Silicon dioxide layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Equations (3) through (12) have been adopted from the existing literature [ 3 , 53 , 54 , 55 , 56 , 57 ]: …”
Section: Electromagnetic Circuit Simulation Analysis Of Mosfet-based ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Equations (3) through (12) have been adopted from the existing literature [ 3 , 53 , 54 , 55 , 56 , 57 ]: …”
Section: Electromagnetic Circuit Simulation Analysis Of Mosfet-based ...mentioning
confidence: 99%
“…The MOSFET-based absorber schematic is presented in Figure 12 . In order to complete the rectification process while taking into account the ON and OFF states of the diodes and the potentials at each node of the rectifier, it has been demonstrated that the absorber is a combination of an RLC filter, an N-channel MOSFET, and a four-diode combination [ 55 , 56 , 57 ]. The function of the RLC filter, in this case, is to reduce the pulses at the output of the rectifier; this allows for maximum performance of the MOSFET device in the absorber.…”
Section: Electromagnetic Circuit Simulation Analysis Of Mosfet-based ...mentioning
confidence: 99%
“…The potential involved with the cylindrical structure has been affected by an imaginary capacitor and it is termed 'V'. This potential exists between the concentric layers of the cylindrical structure of the CSDG MOSFET [2][3][4][5][6]. The inner layer of the cylinder has a radius of rc 2 and the outer layer of the cylinder has a radius of rc 1 .…”
Section: A the Concentric Cylindrical Modelmentioning
confidence: 99%
“…Silicon is still a suitable material to design complex nanostructures. The heterostructures were designed using the arbitrary alloy of semiconductors and found their applications in nano-photonics, wearable nanomaterial gadgets, and opto-electromechanics [2]. Further research reveals that the latest technology supports the patterning of the heterostructures with proper resolution and higher fidelity with precision.…”
Section: Introductionmentioning
confidence: 99%
“…Opto-genetics, or optical stimulus, is considerably more favorable to cells. Furthermore, an electro-optic stimulus needs large expression levels of foreign transmembrane ion-conducting proteins, implying that perhaps the researcher must modify a cell in order to influence its behavior [ 10 , 11 , 12 , 13 ]. Recent breakthroughs in nanotechnology have facilitated the development of integrated Nano-Particle Systems (NPS) on various substrates that have been shown to be a new generation platform for studying and controlling cellular function at the cell-device level.…”
Section: Introductionmentioning
confidence: 99%